Predicting Swell in Clay-Sand Mixtures Used in Liners - Muawia Dafalla (Applied Sciences, 2023)
A method to predict the swellability of clay-sand mixtures is proposed. This model is a modified form of the Studds (1997) prediction model for clay-sand mixtures. The new proposed model uses the laboratory fall cone penetration technique to produce a characterization chart. This chart presents slope levels that can be used to obtain an equation for the final clay void ratio versus the vertical effective stress for clays. The porosity of the clay-sand mixtures was worked out based on a correction factor obtained from compression and porosity measurements in the laboratory. The porosity of the mixture was merged into the clay profile equation to compute the final clay void ratio at a specified stress level, which made it possible to predict the swelling behavior for different and variable stress levels. The swellability slope was obtained using fall cone tests conducted on the fine portion. Mixtures of kaolinite and bentonite were introduced to represent soils with different swell potentials. The fall cone measurements of a few points can be used to establish the swellability relationships for natural clay. Merging fall cone points with the swellability slope chart can define the profile of the vertical effective stress versus the clay void ratio.